Co-silencing of human Bub3 and dynein highlights an antagonistic relationship in regulating kinetochore-microtubule attachments - Silva, Patricia M. A. (2018)
We previously reported that the spindle assembly checkpoint protein Bub3 is involved in regulating kinetochore-microtubule (KT-MT) attachments. Also, Bub3 was reported to interact with the microtubule motor protein dynein. Here we examined how this interaction contributes to KT-MT attachments. Depletion of Bub3 or dynein induced misaligned chromosomes, consistent with their role in KT-MT attachments. Unexpectedly, co-silencing of both proteins partially suppressed the misalignment phenotype and restored chromosome congression. Consistent with these observations, KT-MT attachments in co-depleted cells were stable, able to drive chromosome congression, and produce inter-and intra-kinetochore stretch, indicating they are functional. We suggest that a mutual antagonism exists between Bub3 and dynein to ensure optimal KT-MT attachments. (C) 2015 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.